Writing history in the digital age - Dougherty, Jack; Nawrotzki, Kristen (Digital humanities (Ann Arbor, Mich.), 2013)
"Writing History in the Digital Age began as a one-month experiment in October 2010, featuring chapter-length essays by a wide array of scholars with the goal of rethinking traditional practices of researching, writing, and publishing, and the broader implications of digital technology for the historical profession. The essays and discussion topics were posted on a WordPress platform with a special plug-in that allowed readers to add paragraph-level comments in the margins, transforming the work into socially networked texts. This first installment drew an enthusiastic audience, over 50 comments on the texts, and over 1,000 unique visitors to the site from across the globe, with many who stayed on the site for a significant period of time to read the work. To facilitate this new volume, Jack Dougherty and Kristen Nawrotzki designed a born-digital, open-access platform to capture reader comments on drafts and shape the book as it developed. Following a period of open peer review and discussion, the finished product now presents 20 essays from a wide array of notable scholars, each examining (and then breaking apart and reexamining) how digital and emergent technologies have changed the ways that historians think, teach, author, and publish"--